Scientific Thought and Material Culture. On the Strategies for Practicing History of Science on the Example of the Birth of Mathematical Physics as Seen by Wiesław Ozon - Falkowski, Tomasz (Sensus Historiae, 2022)
In the proposed text I mention one of the most interesting theoretical approaches to the history of science, developed in Poland at the end of the 20th century. Wiesław Ozon was the author of a small number of works; he died at a young age, at the threshold of his academic career. However, his book Powstanie fizyki matematycznej [The Birth of Mathematical Physics] deserves close attention for many reasons. I mean here above all: (1) consistent connecting of theoretical dimension with empirical material; (2) the application of the author’s middle range theory to the attempt to understand a specific phenomenon from the history of science; (3) the inclusion of the material dimension of reality and its changing nature in the formulated concept. Ozon's main thesis, which states that the basic condition for the mathematization of reality in the first half of the 17th century (the works of Galileo, Descartes, Newton) were the changes occurring at that time in material culture and the world of things, or more precisely: the larger-scale appearance of the so-called abstract objects, constitutes part of the ongoing discussion on the ways of practicing the history of science, as it occupies a specific position both in the dispute between internalism and externalism, and in the “return to things” postulated by some researchers.